Direct Carbon Fuel Cells: Dual 3D Ceramic Textile Electrodes: Fast Kinetics for Carbon Oxidation Reaction and Oxygen Reduction Reaction in Direct Carbon Fuel Cells at Reduced Temperatures (Adv. Funct. Mater. 19/2020). (11th May 2020) - Bian, Wenjuan; Wu, Wei; Orme, Christopher J.; Ding, Hanping; Zhou, Meng; Ding, Dong
Abstract : In article number 1910096, Wei Wu, Meng Zhou, Dong Ding, and co‐workers report a direct carbon fuel cell (DCFC) with dual‐3D ceramic textile (3DCT) electrodes operating at 600 °C and below. The dual 3DCT electrodes enable efficient mass and charge transfer to accelerate electrochemical reaction kinetics in both the anode and cathode, leading to superior DCFC performance at reduced temperatures.